2021
DOI: 10.3390/ani11020540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacterial or Fungal Phytase Supplementation on the Performance, Egg Quality, Plasma Biochemical Parameters, and Reproductive Morphology of Laying Hens

Abstract: Catalytic and physicochemical properties of microbial phytase sources may differ, affecting phosphorus (P) release and subsequently the productive and reproductive performance of layers. The current study aimed to evaluate the impact of bacterial and fungal phytase sources on layer productivity, egg production, biochemical blood indices, and reproductive morphology. For this purpose, 360 Bovans brown hens at 42 weeks of age were randomly allocated into 4 experimental groups, each with 15 replicates of 6 hens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In the current study, feeding with OCM increased the vitamin E level of the muscles in birds, which may lead to a reduction in the lipid peroxidation process in the birds and, as a result, reduce the oxidation status [ 36 ]. Since the essence of the diet has a direct relationship with oxidative damage in cultured organisms, oxidative focus occurs when the development and removal processes of free radicals (ROS) are unbalanced [ 39 , 40 ]. Reactive oxygen species (ROS) scavengers, such as superoxide dismutase, glutathione peroxidase, and catalase, protect body tissues from oxidative stress [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, feeding with OCM increased the vitamin E level of the muscles in birds, which may lead to a reduction in the lipid peroxidation process in the birds and, as a result, reduce the oxidation status [ 36 ]. Since the essence of the diet has a direct relationship with oxidative damage in cultured organisms, oxidative focus occurs when the development and removal processes of free radicals (ROS) are unbalanced [ 39 , 40 ]. Reactive oxygen species (ROS) scavengers, such as superoxide dismutase, glutathione peroxidase, and catalase, protect body tissues from oxidative stress [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between eggshell and bone quality may be different in various conditions since eggshell and bone quality were also influenced by diets and environmental factors [ 6 9 , 31 , 42 ]. Our previous study suggested that eggshell quality exhibited simultaneous improvements with bone quality by changing a conventional caging system to an aviary system [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These hens laying weak-shelled eggs deserve special attention since they are responsible for a high breakage rate of eggs at the late laying period. Nutritional modulation strategies have been widely recognized as positive means of improving egg, especially eggshell, quality [ 6 9 ]. Comparison of eggshells and physiological characteristics of hens with high and low eggshell breaking strength could reveal the mechanism of increased egg breakage rate in aged laying hens, which is beneficial to develop more suitable products or measures for eggshell quality improvement.…”
Section: Introductionmentioning
confidence: 99%
“…To fulfill the requirements of phosphorous for the birds, monocalcium phosphate (MCP) or dicalcium phosphate (DCP) in the form of inorganic phosphorous may be supplemented to the poultry feed. But, in this way, the cost of feed and the amount of P released in the form of excreta will be increased causing environmental pollution (Saleh et al, 2021). To deal with such problems, supplementation of phytase in the bird's feed is a suitable solution (Lalpanmawia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%